Daya Hambat Aktivitas Enzim Glukosiltransferase (Gtf) Streptococcus mutans Oleh Ekstrak Temulawak (Curcuma Xanthorrhiza Roxb.) - A. Amanda; Sri Kunarti; Agus Subiwahjudi (Universitas Airlangga, 2017)
Background: Streptococcus mutans is a bacteria which has glucosyltransferase (GTF) enzyme and acts as the main agent that causes dental caries. GTF enzyme will convert sucrose into fructose and glucan. Temulawak (Curcuma xanthorrhiza Roxb.) is one of the traditional herbs which has xanthorrhizol, curcumin, flavonoid, tanin, and saponin as an antibacterial agent. Purpose: The purpose of this research is to investigate the effect of temulawak extract (Curcuma xanthorrhiza Roxb.) to the activity of GTF enzyme Streptococcus mutans. Method: This research used 25%, 37,5%, and 50% concentration of temulawak extract as the treatment, and 0.12% chlorhexidine gluconate as a control. The method of this research consists of three steps; preparing the temulawak extract concentration of 25%, 37,5%, and 50%, preparing the GTF enzyme from the supernatant of Streptococcus mutans, and testing GTF enzyme activity by analyzing the fructose concentration using High Performance Liquid Chromatography (HPLC). Perusal of the fructose area was based on the retention time of fructose. One unit of GTF enzyme activity is defined as the 1 μmol fructose / ml of enzyme / hour. Result: The obtained data then were analyzed by Post-Hoc Tukey (HSD). The result showed a significant difference between each treatment group with the control group (p<0.05). Conclussion: This research concludes that temulawak extract with 25%, 37,5%, and 50% concentrationcan’t inhibit the GTF enzyme activity of Streptococcus mutans.